'Crocodiles in the Corridors': Security Vetting, Race and Whitehall, 1945–1968. Issue 1 (2nd January 2021) - Lomas, Daniel W. B.
ABSTRACT: In July 2018, the UK's Intelligence & Security Committee issued a report into diversity and inclusion across the intelligence and security community. The picture the report painted was far from satisfactory; in short, Britain's intelligence agencies did not 'fully reflect the ethnic make-up of modern Britain'. The report argued that Britain's spy agencies – MI5, SIS (or MI6) and GCHQ – should improve black, Asian and ethnic minority recruitment, highlighting areas for improvement, especially around the vetting of recruits. This problem stems from the post-war Cold War 'security state' and the development of security-vetting programmes from the 1940s, aiming to protect Whitehall from Soviet spies and 'fellow travellers' to those with so-called 'character defects'– drink, drugs and homosexuality. But this 'security state' also saw the newly emerging multicultural Britain as a major threat. The so-called 'Windrush Generation' of migrants from the Caribbean, and migration from the Indian subcontinent and Africa, forever changed the social complexion of Britain, but posed significant questions for security officials. What was Britishness? With first or second generation migrants entering the civil service, who was a 'UK eye' and what access to secret information should they have? To what extent was discrimination justifiable to protect state secrets, and how should officials respond to new legislation such as the Race Discrimination Act? As this article shows, new entrants to the civil service faced deeply engrained prejudices, and questions over their loyalty to Britain. As late as the 1960s (and beyond), 'coloured' members of the civil service were rejected from secret posts across government, including the Ministry of Defence and intelligence and security services, especially MI5 and GCHQ, with discrimination on 'security' grounds justified by the landmark 1968 Race Relations Act, which barred race discrimination for housing and employment elsewhere.